2022
DOI: 10.1111/vec.13182
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of acute salbutamol (albuterol) exposure in dogs: 501 cases

Abstract: Objective: To determine the common clinical signs, with onset and duration, treatments given, and outcome in dogs with acute, accidental exposure to salbutamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It is possible the incidence of adverse effects could increase with higher doses of albuterol IH in dogs. This theory is supported by the results from 2 recent retrospective studies that revealed tachycardia (81%‐94%), hypokalemia (21%‐69%), and hyperglycemia (67%) were common sequela to intoxication by high‐dose salbutamol (albuterol) exposure in dogs 40,41 …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is possible the incidence of adverse effects could increase with higher doses of albuterol IH in dogs. This theory is supported by the results from 2 recent retrospective studies that revealed tachycardia (81%‐94%), hypokalemia (21%‐69%), and hyperglycemia (67%) were common sequela to intoxication by high‐dose salbutamol (albuterol) exposure in dogs 40,41 …”
Section: Discussionmentioning
confidence: 72%
“…This theory is supported by the results from 2 recent retrospective studies that revealed tachycardia (81%-94%), hypokalemia (21%-69%), and hyperglycemia (67%) were common sequela to intoxication by high-dose salbutamol (albuterol) exposure in dogs. 40,41 This study had several limitations that require further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Albuterol, a selective ß2‐adrenergic agonist, is used for its bronchodilator effects in the treatment of asthma in human, canine, and feline patients 1 . Albuterol toxicosis is encountered in veterinary medicine, as dogs tend to chew on albuterol‐containing inhalers, resulting in sudden massive exposures 2 . Acute toxicosis can result in significant clinical and laboratory abnormalities, including cardiac arrhythmias, weakness, hypokalemia, hypomagnesemia, hyperglycemia, and hyperlactatemia 1–4 .…”
Section: Introductionmentioning
confidence: 99%
“…These effects are mediated by the stimulatory effects of ß2‐adrenergic agonists on the pancreatic islet cells and cell membrane Na/K‐ATPase pumps, as well as the direct increase in glycogenolysis 3,5 . With extreme overdoses, specificity for the ß2 receptor is decreased, and albuterol binds to both ß1 and ß2 receptors 2,3 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation